A new variety of Musa balbisiana Colla from Assam, India - Borborah, Kongkona; Borthakur, S. K.; Tanti, Bhaben (Bangladesh Journal of Plant Taxonomy, 2016)
Not available. Bangladesh J. Plant Taxon. 23(1): 75-78, 2016 (June)